1.
(х+1)² + x + 1 = (x+1)(x+2)
х² + 2х +1 + х + 1 = x² + x + 2х + 2
х²+3х+2 = х²+3х+2
0 = 0 при любом х выполняется равенство
Ответ: х ∈ (-∞; +∞)
2.
x(x-5)/0,3=0
0,3 · x(x-5)/0,3=0
,3 · 0
x·(x-5) = 0
x₁ = 0
x-5 = 0 => x₂=5
Ответ: {0; 5}
3.
![\frac{1}{3}+\frac{x}{2} =\frac{1}{3}x^2\\ \frac{1*6}{3}+\frac{x*6}{2} =\frac{1*6}{2}x^2\\ 2+3x=2x^2\\2x^2-3x-2=0\\\\D=9-4*2*(-2)=9+16=25=5^2\\x_1=\frac{3-5}{4}=-0,5\\x_2=\frac{3+5}{4}=2 \frac{1}{3}+\frac{x}{2} =\frac{1}{3}x^2\\ \frac{1*6}{3}+\frac{x*6}{2} =\frac{1*6}{2}x^2\\ 2+3x=2x^2\\2x^2-3x-2=0\\\\D=9-4*2*(-2)=9+16=25=5^2\\x_1=\frac{3-5}{4}=-0,5\\x_2=\frac{3+5}{4}=2](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%2B%5Cfrac%7Bx%7D%7B2%7D%20%3D%5Cfrac%7B1%7D%7B3%7Dx%5E2%5C%5C%20%5Cfrac%7B1%2A6%7D%7B3%7D%2B%5Cfrac%7Bx%2A6%7D%7B2%7D%20%3D%5Cfrac%7B1%2A6%7D%7B2%7Dx%5E2%5C%5C%202%2B3x%3D2x%5E2%5C%5C2x%5E2-3x-2%3D0%5C%5C%5C%5CD%3D9-4%2A2%2A%28-2%29%3D9%2B16%3D25%3D5%5E2%5C%5Cx_1%3D%5Cfrac%7B3-5%7D%7B4%7D%3D-0%2C5%5C%5Cx_2%3D%5Cfrac%7B3%2B5%7D%7B4%7D%3D2)
Ответ: {- 0,5; 2}